(untitled) (International Journal of Nursing Education, 2022)
Context: Traditional teaching approaches prove to be a viable alternative to video-assisted learning. Teachers areunder-informed about the illness and learning needs of children with mental disorders, notably attention deficithyperactivity disorder.Aim: This study aimed to examine how effectively video-assisted teaching meets the learning needs and literacyof attention deficit hyperactivity disorder among teacher trainees in South India.Settings and Design: Institution-based longitudinal study.Material and Methods: Before and one week after video-assisted teaching about ADHD, 30 randomly selectedtrainee teachers were examined using questionnaires on ADHD literacy and learning need.Statistical Analysis Used: descriptive statistics, ANOVA, and paired-samples t-test.Results: On paired-samples t-test, there was a statistically significant difference in the score of ADHD literacy [t(29) = -18.46, p =.001] and learning needs [t (29) = -32.66, p =.001] pre and post scores.Conclusions: Using video-assisted teaching improves ADHD literacy and the learning needs of children.